Etika Persaingan Bisnis dalam Islam pada Pelaku UMKM: Ethics of Business Competition in Islam for MSME Players - Rizma Nadia Putri; Risma Ratna Safira; Nashwa Callista Mahardika; Asa Sulistyaningsih; Nabila Arsida; Aprilia Rahma Yunan Sari Romodar; Ahmad Nurrohim (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2024)
This study aims to analyse the condition of the ethics of Business Competition in Islam in MSME Actors in Indonesia. Often found fraud that is far from moral values as well as religion. Many business actors are also found that in its implementation is filled with mal-business practices, including all business practices that are not good, bad, bring about losses, or violate the law. This research uses the literature study method or library research, which is a series of data collected and then analysed using the descriptive analytical method with a qualitative approach, where researchers will describe and analyse the concepts of business competition ethics in Islam and its implementation in the MSME sector. The results show that the application of Islamic business ethics shows a good influence, also has a positive effect in improving MSMEs. As for the cases that have been studied between X bread factory and Y chips factory with the discussion of the application of Islamic business ethics in MSMEs, it is very relevant, where it can be seen that Islamic business ethics are not just an additional value, but an integral part of a successful business strategy. By placing ethics as the cornerstone, MSMEs can increase customer loyalty, strengthen reputation, and ultimately achieve sustainability in business.